Ready to help the workers who elected her: Councillor Ilza Gouvêa and the militancy of the weaver women of Magé, Rio de Janeiro state (Tempo e Argumento, 2011)
The period between 1947 and 1964 was a time of rich experiences for the textile workers of the municipality of Magé, in state of Rio de Janeiro. It was regarded by the workers as a golden period of many achievements for workers of their category, especially through political and trade union participation. This context coincided precisely with the rise of the Communist Party of Brazil (PCB) in the city, and several of its militants were elected as union directors and councilors. By promoting a high level of organization and of mobilization of the local workers, the communists managed to secretly elect, under different banners, a total of eleven councillors in Magé. In this context, the study aims to examine the political militancy of the weaver women of Magé, especially the weaver Ilza Gouvêa, who was elected as a councillor in 1950.
Keywords: working women; Communist Party of Brazil; women's political activism; political activism